Effects of Ageratum conyzoides Leaf Decoction on Glucose Absorption in Rat’s Small Intestine - Sakinah, Siti; Dhianawaty, Diah; Tarawan, Vita Murniati (Althea Medical Journal, 2018)
Background: Obesity is one of the health problems caused by excessive glucose intake which exceeds normal body requirement. To prevent health problems, Indonesian natives used traditional herbs, such as Ageratum conyzoides (billygoat weeds). The study aimed to discover the effect of Ageratum conyzoides leaf decoction on glucose absorption in the small intestine of rats.Methods: An experimental study was conducted at the Biochemical Laboratory of Faculty of Medicine, Universitas Padjadjaran. Two groups of six rats were given Ageratum conyzoides leaf decoction with dosages 0.89 and 1.33 g/kgbw respectively. Each rat was given glucose solution as a control, decoction administration along with the glucose solution, and glucose solution again to discover the effect of decoction in the absorption function after the administration of decoction was discontinued. Glucose absorbed by the intestine was measured every 15 minutes in 1 hour after the administrationof the solution.Results: Glucose absorption was impeded in dosage 1 and 2 with a mean of the gap between glucose absorbed concentration before given decoction and after given decoction were 73.97 and 45.09 mg/dl respectively. Analysis using paired t-test resulted in insignificant meaning (p-value of dosage 0.89 g/kgbw=0.08; p-value of dosage 1.33 g/kgbw=0.06). In the last glucose perfusion, absorption increased in both dosages after administration of decoction was discontinued.Conclusions: Ageratum conyzoides leaf decoctioncan inhibit the glucose absorption in the small intestine but is not statistically significant. Further investigation may be needed  by using a higher concentration of Ageratum conyzoides and/or other filtration methods.